Effect of Board Size and Duality on Corporate Social Responsibility: What has Improved in Corporate Governance in Asia? Pengaruh Ukuran Dewan dan Dualitas pada Tanggung Jawab Sosial Perusahaan: Apa yang Telah Meningkat dalam Tata Kelola Perusahaan di Asia? - Alabdullah, Tariq Tawfeeq Yousif; Ahmed, Essia Ries; Muneerali, Mohammed (Universitas Muhammadiyah Sidoarjo, 2019)
The aim of this study is to examine the relationship between board size and CEO duality, and corporate social responsibility (CSR). A total of 91 public listed companies from Bursa Malaysia representing the sample of the current study were selected. Secondary data were used and sourced from annual report on the companies. Using descriptive statistics, the existence and the extent of CSR disclosure on Malaysian companies were ascertained. An analysis of the quantitative data was then made using the Partial Least Squares (PLS). The findings from this research show that the role of board size suggest a significant and positive relationship with CSR disclosure. On the other hand, CEO duality on CSR disclosure indicates a negative relationship. This research contributes to the existing literature in terms of the roles of board Size and CEO duality on CSR initiatives. Furthermore, It highlights the necessity of following the new trends in corporate governance field by investigating its mechanisms with the new trendsin financial Industry from Islamic perspective as this might be positively added to the field of corporate governance due to the high significant role for these two fields.